Senyawa Antibakteri Escherichia coli ATCC 35218 dan Staphylococcus aureus ATCC 25923 dari Kapang Endofit Taman Nasional Gunung Halimun - Melliawati, Ruth; Harni, Harni (Jurnal Natur Indonesia, 2009)
Endophytic fungus is a microorganism which live in the interstitial spaces healthy tissues of the host plant, andhas capability to produce secondary metabolite such as micotoxin, antibiotic and antiviral. This research wasaimed to find out the isolates of endophytic fungus produce antibacterial compounds to inhibit Escerichia coliATCC 35218 and Staphylococcus aureus ATCC 25923, and to investigate the Retention time (Rt) of the antibacterialcompounds produced by endophytic fungus with High Performance Liquid Chromatography (HPLC) methods.Diffusion Agar Plate Method was used to examine the antibacterial compounds on Escerichia coli ATCC 35218 andStaphylococcus aureus ATCC 25923. While the antibacterial compounds were examined with Thin LayerChromatography (TLC) and High Performance Liquid Chromatography (HPLC) methods, and the result werecompared with Chloramphenicol and Ampicillin antibiotic standart. Two isolates of endophytic fungus namelyHl.46F.211 and HL.57F.258 were inhibited the growth Escherichia coli ATCC 35218 and three isolates namelyHL.48F217, HL.53F.243 and HL.57F.258 showed antagonistic action against Staphylococcus aureus ATCC 25923.The results of TLC and HPLC analysing method show that antibacterial compounds produced by endophytic fungusHL.46F.211 had Rt (Retention Time) rate similar with antibiotic Chloramphenicol at 2,796 (at water fraction) and Rtantibiotic Amphycillin at 2,662 (at Chloroform fraction). While antibacterial compounds produced by endophyticfungus HL.57F.258 had Rt rate similar with antibiotic Amphycillin at 2,650 (at Chloroform fraction).